Про могилянський підтекст у діалозі Григорія Сковороди «Брань Архистратига Михаила со Сатаною» - Бартоліні, М.Ґ. (Слово і Час, 2022)
Досліджується єдиний випадок, коли у творчості українського філософа Григорія Сковороди наявне текстове запозичення із двох авторів, що належали до його alma mater, — Варлаама Лящевського та Теофана Прокоповича. У корпусі діалогів цього автора майже цілковито відсутні прямі цитати із сучасників. Тож у статті з’ясовано особливі семантичні конотації, що їх має цей могилянський підтекст, висвітлено проблеми, які він породжує, і міру, до якої ці вставки дають нам змогу глибше зрозуміти зв’язок Сковороди з роками його навчання в Києві. The paper explores Hryhorii Skovoroda’s dialogue “Archistratigus Michael’s Fight with Satan” (“Bran Arkhystratyha Mykhaila so Satanoiu”, 1783), which contains several quotations from two authors — Teofan Prokopovych and Varlaam Liashchevskyi – who belonged to Skovoroda’s Alma Mater, the Kyiv Mohyla Academy. Being a unique occurrence in Skovoroda’s writings, these quotations from contemporary authors have been analyzed as an instance of a peculiar “Mohylian subtext” that sheds light on the relationship between the Ukrainian philosopher and his Alma Mater. In “Bran Arkhystratyha”, the angelic ranks battling against demonic forces sing a song taken from Liashchevskyi’s tragicomedy “The Chased Church” (“Honymaia tserkov”) and from Prokopovych’s 1709 epinikion in honor of tsar Peter’s victory near Poltava. While Prokopovych’s verses have been slightly changed (Antichrist replaces ‘apostate’ — ‘otstupnyk’) to reflect the major theme of “Bran Arkhystratyha” — the fight against Satan — the presence of two fragments from Liashchevskyi’s tragicomedy in the text is even more important, as “Bran Arkhystratyha” is the only available source for reconstructing the textual content of this tragicomedy, of which we do not possess any extant copies. Of particular interest are also the paratextual materials attached to the quotations from Liashchevskyi and Prokopovych. All three citations are accompanied by an explanatory note stating: 1) the author to whom the citation belongs; 2) the authors’ affiliation to the Kyiv-Mohyla Academy; 3) information about the fire that destroyed the library of the Kyiv- Mohyla Academy on February 29, 1780. This choice testifies to a specific urge on Skovoroda’s part to honor Alma Mater and its representatives three years after the fire that threatened its book collection and cultural legacy. In this personal tribute, the notion of memory acquires a specific meaning for, in the case of Liashchevskyi, “Bran Arkhystratyha” preserves a text that would not otherwise have been transmitted. Thus, the ‘victory’ glorified in the dialogue becomes first and foremost a victory against oblivion, through the projection of the Word into the realm of eternity.